CYBER GOVERNMENT PUBLIC RELATIONS MANAGEMENT IN STRENGTHENING THE IMAGE OF THE INFORMATION TECHNOLOGY BOARD AND NATIONAL COMMUNICATION (WANTIKNAS) - Desy Septiyani; Yunita Sari (Universitas prof. Dr. Moestopo (Beragama), 2021)
This study aims: to determine the implementation of cyber Public Relations Wantiknas in strengthening the organization's image, and to determine the role and function of optimal cyber Public Relations management. The theory used is communication management theory Public Relations, Cyber Public Relations, two-way symmetrical communication, computer mediated communication theory, and image theory. The research method used is a case study. The results of the study show that WANTIKNAS has not implemented PR's management optimally which has an impact on the lack of management of cyber public relations, besides that limited human resources and not positioned in a strategic role in WANTIKNAS's internal become obstacles to the implementation of PR's activities in the delivery of information.